Early-onset lung cancer in Asia: a narrative review - De Guzman, Roselle B. (Frontiers in Oncology, 2025)
IntroductionThe incidence of early-onset lung cancer (EOLC), often defined as those that occur in adults under the age of 50, is increasing globally. Asia accounted for almost 76% of EOLC cases worldwide. This presents a challenge given previous limited studies and the socioeconomic implications.MethodsReferences were identified through a PubMed, Scopus and Web of science search for relevant articles published in 2000 to April 2025 using the terms ‘lung carcinoma or cancer’, ‘early-onset’ or ‘young adults’, and ‘Asia’.ResultsEarly-onset lung cancers are more common in female, primarily presenting as adenocarcinoma, and tends to be diagnosed at an advanced stage. There is a high prevalence of potentially targetable genomic alterations: 30-56.3% EGFR mutations and 16.1-50% ALK rearrangements. Comparative analyses show higher prevalence of actionable genetic alterations ROS1, and RET fusions and ERBB2 mutations compared to older patients. Air pollution is a significant risk factor for lung cancer in Asia. MUC16, a transmembrane glycoprotein, is overexpressed in lung cancer, particularly in patients exposed to indoor air pollution. Patients with EOLC exhibit impaired cell-mediated immunity with reduced T cell infiltration. This suggests a potentially limited response to immune checkpoint inhibitor therapies in this patient group.ConclusionThe incidence of EOLC is increasing in Asia. This accounts for 75.9% of global cases. The research conducted in the region are mostly retrospective and, majority are single-institution studies. Due to its unique clinical and molecular features, EOLC requires dedicated research efforts and tailored interventions.